Occurrences related to the priority tourism development zone in Montenegro-Quindío land management plan - Yepes-Quintero, José Luis
This article aims to show the characteristics surrounding the declaration of a priority tourist development zone in the municipality of Montenegro, department of Quindío, based on a series of actions that combine legal arguments, economic aspects, and information of interest due to its importance, allowing the present article to provide an analysis of the tourism practice and the possible advantages for this region, ratifying the situation of tourism in this part of the Andean Area and the repercussions that the declaration of a tourism development zone brings with it. In the development of the article, there will also be a series of tools that will allow building a proper opinion regarding the socioeconomic, environmental, and cultural development of this Quindiano municipality, with the declaration of a priority tourist corridor that connects its urban area with its rural area and the components included in the basic land use plan (PBOT in Spanish).